PENGARUH LATAR BELAKANG SOSIAL, KEMAMPUAN MANAJERIAL DAN PENGALAMAN TERHADAP KINERJA USAHA (STUDI EMPIRIS PADA INDUSTRI KECIL MENENGAH PENGRAJIN DI KOTA BATAM) (Jurnal Tepak Manajemen Bisnis, 2014)
The research was conducted to see the effect of social background, managerial skills and experienceon the performance of the business. The research was conducted in the city of Batam to entrepreneurs in smalland medium industries in the sector artisans of 7business group consisting of industry: shell fish,wood, assesories,batik, handicrafts, woven, and leather. The research was conducted using primary data obtaineddirectly byusing the help of question naires. The method of analysis use dis multiple regression analysis.Based on the analysis, it is known that the social,managerial skills and experience simultan eously affect theperformance of the business. Experience partial effecton business performance.The greater the experience willhave an effectonincreasing business performance, and vice versa, the less experience will affectt the poorperformance of the business. Social background and managerial skills have no effect partially on businessperformance. The coefficient of determinationis equal to 0.257 research. This values hows that 25.7% change inbusiness performance as the dependent variable, influenced by the determinant variables used in the modelstudyth at social background, managerial skills and work experience. while the rest (74.3%) is explained by thevariable sincluded in the model study.Keywords: Business Performance, SocialBackground, ManagerialAbility, Experience.